Eastern Caribbean Sea level rise in global context - Jury, Mark (2026)
[Introduction]: Sea level rise in the east Caribbean has accelerated to 0.6 cm/yr due to the global effects of accumulating greenhouse gases on the thermal expansion of seawater and terrestrial snow ice-melt. [Objective]: This study quantifies the processes driving sea level rise, including changes in landscape and hydrology. Sea level measurements are placed in context to facilitate regional guidance. [Methodology]: The research employs advanced data assimilation and modelling to statistically analyze trends in both time and space, using the east Caribbean Sea level as a metric. [Results]: The analysis suggests a 2050 sea level 40 cm above 1980 baseline, consistent with model projections in 8.5 W/m2 scenario. Inter-annual sea level variability and parabolic trends, driven by tropical ocean warming and depleted snow cover, are prominent. An uptick of thermal expansion and runoff since 2010 is evident from time-depth plots of global sea temperature and salinity anomalies. [Conclusions]: With beach erosion likely, local adaptative measures are outlined that could be employed elsewhere.